2018
DOI: 10.12659/msm.911628
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of 22-Oxa-Calcitriol in Patients with Rheumatoid Arthritis: A Phase II Trial

Abstract: BackgroundCalcitriol (1 alpha, 25-dihydroxy vitamin D3) is a good vitamin D supplement but can cause hypercalcemia. Whereas, 22-oxa-1 alpha, 25-dihydroxy vitamin D3 (22-oxa-calcitriol) has less hypercalcemic activity than calcitriol and is reported to be effective for cell-proliferative diseases. The objective of the study was to compare renal function and blood tests of arthritis patients receiving calcitriol supplements with those receiving 22-oxa-calcitriol supplements.Material/MethodsA total of 369 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Gopinath et al [ 138 ] demonstrated in a RCT that giving 500 IUs of vitamin D 3 daily along with disease-modifying anti-rheumatic drugs (DMARDs) and calcium to RA patients lead to a significantly higher pain relief than those receiving DMARDs and calcium alone. Another study by Li et al [ 139 ] that randomized RA patients to receive 22-oxa-1,25(OH) 2 D 3 or 1,25(OH) 2 D 3 or placebo observed significantly decreased swollen joints and improved Health Assessment Questionnaire Disease Activity Index scores in those receiving 22-oxa-1,25(OH) 2 D and those receiving 1,25(OH) 2 D compared with the placebo group. However, the doses of 1,25(OH) 2 D 3 and 22-oxa-1,25(OH) 2 D 3 used in the study were reported to be 1250 µg per week, which was about 1000 times higher than the therapeutic dose of these compounds and would likely cause toxicity, thus indicating that there might be some type of error, possibly a decimal point error [ 139 ].…”
Section: Vitamin D and Immune-related Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gopinath et al [ 138 ] demonstrated in a RCT that giving 500 IUs of vitamin D 3 daily along with disease-modifying anti-rheumatic drugs (DMARDs) and calcium to RA patients lead to a significantly higher pain relief than those receiving DMARDs and calcium alone. Another study by Li et al [ 139 ] that randomized RA patients to receive 22-oxa-1,25(OH) 2 D 3 or 1,25(OH) 2 D 3 or placebo observed significantly decreased swollen joints and improved Health Assessment Questionnaire Disease Activity Index scores in those receiving 22-oxa-1,25(OH) 2 D and those receiving 1,25(OH) 2 D compared with the placebo group. However, the doses of 1,25(OH) 2 D 3 and 22-oxa-1,25(OH) 2 D 3 used in the study were reported to be 1250 µg per week, which was about 1000 times higher than the therapeutic dose of these compounds and would likely cause toxicity, thus indicating that there might be some type of error, possibly a decimal point error [ 139 ].…”
Section: Vitamin D and Immune-related Diseasesmentioning
confidence: 99%
“…Another study by Li et al [ 139 ] that randomized RA patients to receive 22-oxa-1,25(OH) 2 D 3 or 1,25(OH) 2 D 3 or placebo observed significantly decreased swollen joints and improved Health Assessment Questionnaire Disease Activity Index scores in those receiving 22-oxa-1,25(OH) 2 D and those receiving 1,25(OH) 2 D compared with the placebo group. However, the doses of 1,25(OH) 2 D 3 and 22-oxa-1,25(OH) 2 D 3 used in the study were reported to be 1250 µg per week, which was about 1000 times higher than the therapeutic dose of these compounds and would likely cause toxicity, thus indicating that there might be some type of error, possibly a decimal point error [ 139 ]. Other studies that used vitamin D 2 [ 140 ], vitamin D 3 [ 141 , 142 ], or 1α(OH)D 3 [ 143 ] in the treatment arm failed to demonstrate the efficacy of the intervention.…”
Section: Vitamin D and Immune-related Diseasesmentioning
confidence: 99%
“…Until now, the evidence from prior randomized clinical trials ( 13 15 ) was not sufficient to determine the clinical benefits of VitD supplementation for RA treatment. However, it was confirmed that the serum VitD status was obviously increased by VitD supplementation in VitD-deficient and VitD-sufficient adults, which improved hypovitaminosis D in RA patients ( 16 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…VitD levels are inversely associated with the RA disease activity ( 10 12 ) and VitD has an immunoregulatory function as well ( 9 ), so VitD supplementation is considered to have potential therapeutic benefits for RA. At present, relatively few randomized clinical trials have assessed VitD supplementation in RA ( 13 15 ). An exploratory study suggested that VitD supplementation improved 28 joint disease activity scores based on C-reactive protein (DAS28 (CRP)) in patients without VitD deficiency but did not affect patients with VitD deficiency at baseline ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies as well as systematic reviews have further shown that VDR activation resulted in reduced production of inflammatory cytokines, including IL‐1, IL‐6, TNF‐α and interferon‐γ (Calton, Keane, Newsholme, & Soares, 2015; Villaggio, Soldano, & Cutolo, 2012) as well as suppression of proliferation in pro‐inflammatory cells (Cutolo, Otsa, Uprus, Paolino, & Seriolo, 2007; Yin & Agrawal, 2014). For these reasons, vitamin D, calcitriol or vitamin D analogs show clinical efficacy in patients with autoimmune diseases such as psoriasis (Lebwohl, Ortonne, Andres, & Briantais, 2009; Perez, Raab, Chen, Turner, & Holick, 1996), rheumatoid arthritis (Li et al, 2018), and multiple sclerosis (Burton et al, 2010).…”
Section: Introductionmentioning
confidence: 99%